Pembelajaran Kosa Kata Secara Insidental (Pada Anak) Melalui Film Kartun Berbahasa Inggris - Makasau, Rosmayasinta (Jurnal Masalah Pastoral, 2017)
Children today are growing surrounded by media and new technology. Television and computers have become necessities in providing children with some excited learning strategies. Children tend to learn effectively through direct experience, where they can see and relate an object within their environment. By providing them with exposures to English conversation in an enjoyable manner, and by familiarizing them with second language vocabularies, they are helped to communicate in the target language more positively. Watching cartoons is indeed a ‘happy experience’ for the young children and it provides an attractive and enjoyable learning environment. English cartoons are seen to promote exposure to English language. This 8 months study tried to provide the result of how English cartoons have accelerated a five years old child’s incidental English vocabulary learning, and provide opportunity to the child to learn new English vocabulary.